Prevalence of Mycoplasma genitalium in Asymptomatic Patients Attending a Department of Genitourinary Medicine: A Consecutive Series - Dabashis Mandal; Priya Pulickal; Gaynor Roberts; Chris Helm; Sarena Bhargava; Cyreline Tan; Hugo C. van Woerden (JEADV Clinical Practice, 2026)
ABSTRACT Background Mycoplasma genitalium is a sexually transmitted infection (STI) linked to urogenital symptoms, pelvic inflammatory disease, and infertility in females. However, in accordance with British Association for Sexual Health and HIV (BASHH) guidelines, it is not routinely included in STI screening panels for asymptomatic individuals attending the genitourinary clinic due to limited evidence on the utility. Objectives The aim of the study is to calculate the prevalence and risk factors for M. genitalium infection in asymptomatic patients attending the genitourinary clinic in the Isle of Man in order to determine a high‐risk population which may benefit from screening. Methods Asymptomatic individuals attending the genitourinary clinic in the Isle of Man were identified and recruited following the completion of a routine clinic questionnaire. Self‐taken vaginal swabs or first‐void urinary samples were tested using an Aptima assay, which uses transcription‐mediated amplification. Risk factors for the infection were assessed by analysing clinician‐completed histories detailing demographics and clinical characteristics. Results The total number of participants was 251 with 100% retention. The prevalence of infection was 4.38% (11/251; 95% binomial CI 2.21%–7.71%), with a higher rate of infection in those aged 30 year and younger (prevalence 7.14% (10/140; binomial 95% CI 3.48%–12.74%). Non‐statistically significant associations included female gender and non‐British ethnicity. Conclusions The prevalence of M. genitalium in asymptomatic individuals attending the genitourinary clinic is significant. M. genitalium testing those aged